When China rules the world : the end of the western world and the birth of a new global order - Jacques, Martin (New York : Penguin Press, 2009)
Explains how China's ascendance as an economic superpower will alter the cultural, political, social, and ethnic balance of global power in the twenty-first century, unseating the West and in the process creating a whole new world.
The changing of the guard -- The rise of the West -- Japan : modern but hardly western -- China's ignominy -- Contested modernity -- China as an economic superpower -- A civilization-state -- The Middle Kingdom mentality -- China's own backyard -- China as a rising global power -- When China rules the world -- Concluding remarks : the eight differences that define China.
Includes bibliographical references (p. 438-539) and index.
Keywords: Globalization -- Economic aspects -- China; China -- Foreign relations -- 1976-; China -- Politics and government -- 2002-; China -- Economic conditions -- 2000-; China -- Foreign relations -- Western countries; Western countries -- Foreign relations -- China